Factores maternos y fetales asociados al parto pretérmino en pacientes atendidas en el Hospital San Vicente de Paul de la ciudad de Pasaje. - Rivera Salas, Javier Alexander (2016)
Each year are born in the world around 13 million premature infants and the vast majority of them are born in poor countries. The preterm labor and preterm birth remains one of the most common complications in obstetrics, despite the great advances of modern medicine, so it is a challenge and continuous point of attention. This study was descriptive, transversal and ambispective type, in which 64 patients who met the criteria for inclusion and exclusion treated in the service of Gynecology and Obstetrics Hospital San Vicente de Paul, during the December 2015 period were studied - August 2016. The objectives of this research work were to determine the main factors in maternal and fetal preterm delivery. In the present study found that the most frequent causes of preterm delivery were with 64.1% were the lack of prenatal checkups, the intergenesic period also plays an important role with 37.5%, also found that 76.6% of patients had less than three factors associated with preterm birth, fetal concerning factors include premature rupture of membranes which meant a 26.6% which were not relevant in the present study. Concluding that the most important factor in maternal preterm labor is the lack of prenatal checkups. Keywords: birth, maternal, fetal, factors